(untitled) (The Review of Diabetic Studies, 2024)
Background Radiation protection aims to reduce unnecessary exposure to X-ray radiation, protecting patients and healthcare workers. Although diagnostic imaging techniques contribute minimally to overall exposure, risks still exist. Radiologic technologists and nursing perform X-ray procedures in diverse settings, collaborating with medical teams to ensure quality patient care. X-ray imaging is a common procedure performed on a regular basis for diagnostic purposes all over the world. The use of X-rays is increasing rapidly with the introduction of new radiation-oriented therapeutic practices. Although it carries significant diagnostic benefits, extensive exposure to X-ray imaging has been shown to be associated with multiple dose-dependent health risks. Plain X-Ray is a common procedure performed on a regular basis for diagnostic purposes all over them world. The use of Plain X-Ray, Resonance Imaging is increasing rapidly with the introduction of new radiation-oriented therapeutic practices. Awareness and knowledge among radiographer nurses regarding the effects of X-ray imaging, therefore, becomes important. Aim of the study: To assessment the knowledge of radiologic technologist’s image interpretation X-ray among radiographer nurses in Saudi Arabia 2024. Methods: This cross-sectional study was conducted from Public Sector Hospitals kingdom of Saudi Arabia, convenience sampling technique was adapted to recruit 200 participants for the study. A pretested questionnaire was used to assess the knowledge of radiation among nursing, radiographer and health care workers their perception regarding the necessary safety measures required to be undertaken during the X-ray imaging procedure. .Health care working in X-Ray, department It includes questions on socio demographic variables, knowledge of regarding during the January to April 2024. Results: majority of participant (4.0%0) have average of the knowledge towards risks Associated with the Use of X-Ray followed by (38.0%) of participant high but weak were (22.0%) while Range(7 -18) and Mean ±SD(11.287±2.247) X2 23.360 and a significant relation P=0.001. Conclusion: The radiographer nurses working in the public sector care hospitals of Saudi Arabia seem to lack the knowledge and awareness regarding the hazards of ionizing radiations and the necessary safety measures required to be undertaken during X-ray imaging. More awareness programs should be conducted to increase the level of radiographer nurses awareness to protect them from unnecessary health risks.